DYT2 screening in early-onset isolated dystonia. (March 2017) - Carecchio, Miryam; Reale, Chiara; Invernizzi, Federica; Monti, Valentina; Petrucci, Simona; Ginevrino, Monia; Morgante, Francesca; Zorzi, Giovanna; Zibordi, Federica; Bentivoglio, Anna Rita; Valente, Enza Maria; Nardocci, Nardo; et al.
Abstract: Background: Mutations in HPCA, a gene implicated in calcium signaling in the striatum, have been recently described in recessive dystonia cases previously grouped under the term "DYT2 dystonia". Positive patients reported so far show focal onset during childhood with subsequent generalization and a slowly progressive course to adulthood. Methods: 73 patients with isolated dystonia of various distribution, manifesting within 21 years of age, were enrolled in this Italian study and underwent a mutational screening of HPCA gene by means of Sanger sequencing. Results/conclusions: Mean age at onset was 10.2 (±5.1) years and mean age at the time of genetic testing was 33 (±14.2) years. Mean disease duration at the time of enrollment was 22.7 (±12.8) years. None of the patients enrolled was found to carry HPCA mutations, rising suspicion that these probably represent a very rare cause of dystonia in childhood-adolescence. Larger studies will help determining the real mutational frequency of this gene also in different ethnic groups. Highlights: Early-onset dystonia is a genetically heterogeneous movement disorder. Mutations in Hippocalcin ( HPCA ) cause recessive dystonia with onset in childhood. Out of 73 early-onset dystonia patients, none resulted positive for HPCA mutations. HPCA mutations are probably a very rare cause of recessively-inherited dystonia.